Hubungan Tingkat Pendidikan Ibu dengan Penerapan Stimulasi Perkembangan pada Anak Usia Prasekolah - Febrianti, Tressia; Hawara, Gian (JURNAL KEPERAWATAN RAFLESIA, 2024)
Stimulation is an important factor in children's growth and development. Early intervention by providing stimulation can provide maximum results in children because interaction between children and parents can improve neural connections in the child's brain. This study aimed to analyze the relationship between a mother's education level and the application of child development stimulation. This study used a quantitative research design with a descriptive correlational method through a cross-sectional study approach on 242 respondents with the inclusion criteria of mothers who can read and write and pre-school children aged 48–72 months. The research instrument used in this study was the completion of a questionnaire on the mother's education history and child development stimulation guidelines by the Indonesian Ministry of Health (2014). The study was conducted in Bengkulu City in May 2022. The results of the chi-square analysis obtained p-value =0,002 (